Antibacterial activity of tekelan leaf ethanol extract (Chromolaena odorata (L.) R. M. King and H. Rob) against of Staphylococcus aureus bacteria - Harahap, Nurul Dahlia; Dalimunthe, Aminah; Bangun, Hakim (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Indonesia is a tropical country, so the prevalence of infectious diseases caused by bacteria still remains high. On the other hand, the intense use of antibacterial agent in Indonesia causes a tendency for bacterial resistance to existing antibacterial drugs. One of the herbal plants that is widely used by some people is tekelan leaves. The purpose of this study was to determine the activity of an ethanol extract of tekelan leaves on the growth of Staphylococcus aureus bacteria. Methods: Simplisia of tekelan leaves was tested for secondary metabolites and simplisa characterization testing. Antibacterial activity testing is carried out by the disc paper method, where the disc paper is immersed in the test solution with a comparison of the test concentration. Results: The results of phytochemical screening show that the secondary metabolites of tekelan leaves are alkaloids, flavonoids, steroids/triterpenoids, tannins, and glycosides. The results of the characterization of simplisia moisture content are 7.99%, water-soluble juice content is 13.29%, ethanol-soluble juice content is 12.18%, total ash content is 7.45%, and insoluble acid ash content is 0.92%. The observation of the antibacterial activity of the ethanol extract of tekelan leaves was carried out by the disc diffusion method. The test results showed that the ethanol extract of tekelan leaves was categorized as moderate at concentrations of 1% and 2% and as strong at concentrations of 4%, 5%, 10%, 20%, 40%, 60%, 80%, and 100%. The conclusion of this study is that ethanol extract had activity to inhibit the growth of Staphylococcus aureus and the MIC value obtained 0.7%. Conclusions: The conclusion of this study is that ethanol extract had activity to inhibit the growth of Staphylococcus aureus.